Numerical Analyses of Tunnel Outlet Slope at Leuwikeris Dam, West Java, Indonesia - Sunardi Sunardi; I Gde Budi Indrawan; Ardian Baroto Murti (Journal of Applied Geology, 2022)
The excavated slope of the diversion tunnel outlet at the Leuwikeris Dam was designed based on core test data and the Circular Failure Chart (CFC) method. Stability of the excavated slope under static and seismic loads has not been verified using a different method. The objective of this research was to evaluate performance of the excavated slope under static and seismic loads using the finite element method (FEM).  Stability analyses of the natural slope were also carried out to assess the improved stability of the slope after excavation. Geological mapping, examinations of drill cores and borehole logs, and laboratory tests were conducted to characterise the soils and rocks comprising the tunnel outlet slope. The rock masses were characterised using the Geological Strength Index (GSI) for the input parameters of the Generalised Hoek-Brown criterion. The slope stability analyses under static and seismic loads were performed using the finite element-based computer package RS2. The results show that the diversion tunnel construction site consists of residual soil and very poor to fair quality andesite breccia rock and tuff breccia with thin claystone intercalation. The groundwater table was located approximately 40 m below the ground surface. In general, the seismic load reduced stability of the slopes. The critical strength reduction factor (SRF) values of the natural portal slope, which had 40º inclination, were 3.6 and 1.45 under static and seimic loads, respectively. Meanwhile, the SRF values of the excavated slope, which had seven benches and 55 to 74º inclinations, were 3.83 and 1.78 under static and seismic loads, respectively. The natural and excavated slopes were considered stable under static and seismic loads and met the stability criteria specified by the National Standardization Agency (2017). The slope design increased the slope FS values by 6% and 20% under static and seismic loads, respectively.